Marketing Mix - An Area of Unethical Practices? - Bouguila Siham, Dr. (British Journal of Marketing Studies, 2013)
In this paper we intend to develop the concept of ethic in marketing so the first section is concerned with presentation of the components of marketing and how each of them can subject of unethical practices. We try also to discuss some relevant issues related to the same. In the second section we focus on empirical study in order to show that many unethical marketing practices may be occurred especially which are related to pricing and advertizing practices.